2013
DOI: 10.1007/s11764-013-0281-y
|View full text |Cite
|
Sign up to set email alerts
|

Physician preferences and attitudes regarding different models of cancer survivorship care: a comparison of primary care providers and oncologists

Abstract: PCPs and oncologists have different preferences for models of cancer survivorship care. Prior involvement with cancer surveillance was one of the strongest predictors of PCPs' willingness to assume this responsibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(146 citation statements)
references
References 31 publications
7
136
2
1
Order By: Relevance
“…Indeed, for some oncologists, the relationships they develop with patients during the treatment period can make it difficult to transfer responsibility for care back to pcps in the community [22][23][24] . Medical oncologists have described a sense of responsibility during the follow-up period with respect to long-term toxicities and the survivor's compliance with ongoing therapies (for example, endocrine therapy) 24 ; other oncologists have questioned the ability of pcps to provide cancer-related care for survivors 25,26 . On the other hand, survivors are often confused over who is primarily responsible for cancer follow-up care [27][28][29] and uncertain about whether community-based providers have the expertise required to manage cancer follow-up 22,30 , both of which can contribute to concerns about discharge after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, for some oncologists, the relationships they develop with patients during the treatment period can make it difficult to transfer responsibility for care back to pcps in the community [22][23][24] . Medical oncologists have described a sense of responsibility during the follow-up period with respect to long-term toxicities and the survivor's compliance with ongoing therapies (for example, endocrine therapy) 24 ; other oncologists have questioned the ability of pcps to provide cancer-related care for survivors 25,26 . On the other hand, survivors are often confused over who is primarily responsible for cancer follow-up care [27][28][29] and uncertain about whether community-based providers have the expertise required to manage cancer follow-up 22,30 , both of which can contribute to concerns about discharge after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers include lack of role clarity/role delineation, debates regarding the best follow-up strategy, differing perspectives on who should provide what care; and the type and timing of information (Grunfeld & Earle, 2010;Cheung et al, 2013;Del Guidice, Grunfeld, Harvey, Piliotis & Verma, 2009;Haq et al, 2013;Mao et al, 2009;McCabe & Jacobs, 2012;Nissen et al, 2007). The interface between primary care physician and specialist oncologists is where gaps exist at present.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized by Cheung et al (2013) and supported by other authors (Ackerman et al, 2014;Dawes et al, 2015;Del Guidice et al, 2009;Nissen et al, 2007;Salz et al, 2012) that primary care physicians may not be equipped with the knowledge, education, and experience to confidently handle issues and provide adequate follow-up care (to include surveillance testing for cancer recurrence) for complex disease groups. However, many studies in Canada and from other parts of the world have shown that the primary care physician remains the primary coordinator of care during cancer survivorship, and that care can effectively be provided by the primary care physician for low-risk cancer groups (Del Guidice et al, 2009;Mao et al, 2009;Grunfeld et al, 1995Grunfeld et al, , 1996Grunfeld et al, , 1999Grunfeld et al, , 2006Sisler, Brown & Stewart, 2004;Wattchow et al, 2006;Wood, 1993).…”
Section: Role Delineationmentioning
confidence: 99%
“…Oncologists might also be reluctant to completely transition follow-up care to pcps. In fact, prior research has shown that oncologists lack confidence in the ability of pcps to detect recurrence and to care for late effects of cancer treatment 18 and that most do not believe that pcps should be responsible for follow-up care 19 . Multiple-provider follow-up care might also be a result of confusion on the part of providers and survivors alike about who is responsible for follow-up care.…”
Section: Discussionmentioning
confidence: 99%